Stem Cell Therapy: A Promising Approach in Treatment of COVID-19 - Abbaspanah, Bahareh; Abroun, Saeid; Zarrabi, Morteza; Mozdgir, Ashkan; Mollanouri, Mohammad (Current Stem Cell Research & Therapy, 2021)
COVID-19 pandemic is a global health crisis of the 21st Century. There are currently no approved vaccines and no particular anti-viral treatment for coronavirus disease. As COVID-19 has a broad range of illnesses, it is necessary to find a safe and effective therapeutic method for COVID-19. An attractive approach for treating COVID-19 is cell therapy. Cell therapy aims to inject new and healthy stem cells into a patient’s body, to repair the damaged cells and tissues. Stem cell therapy is one of the most studied and important approaches in the treatment of COVID-19 these days. The significant clinical outcome was observed by the adoptive transfer of stem cells, specifically mesenchymal stem cells. This study reviews the characteristics of stem cells and clinical trials that have used stem cells in treating COVID-19.
Keywords: coronavirus